Nutrient-Limited Enrichments of Nitrifiers From Soil Yield Consortia of Nitrosocosmicus-Affiliated AOA and Nitrospira-Affiliated NOB - Rodriguez, Jonathan; Chakrabarti, Seemanti; Choi, Eunkyung; Shehadeh, Nisreen; Sierra-Martinez, Samantha; Zhao, Jun; Martens-Habbena, Willm (Frontiers in Microbiology, 2021)
The discovery of ammonia-oxidizing archaea (AOA) and complete ammonia-oxidizing (comammox) bacteria widespread in terrestrial ecosystems indicates an important role of these organisms in terrestrial nitrification. Recent evidence indicated a higher ammonia affinity of comammox bacteria than of terrestrial AOA and ammonia-oxidizing bacteria (AOB), suggesting that comammox bacteria could potentially represent the most low-nutrient adapted nitrifiers in terrestrial systems. We hypothesized that a nutrient-limited enrichment strategy could exploit the differences in cellular kinetic properties and yield enrichments dominated by high affinity and high yield comammox bacteria. Using soil with a mixed community of AOA, AOB, and comammox Nitrospira, we compared performance of nutrient-limited chemostat enrichment with or without batch culture pre-enrichment in two different growth media without inhibitors or antibiotics. Monitoring of microbial community composition via 16S rRNA and amoA gene sequencing showed that batch enrichments were dominated by AOB, accompanied by low numbers of AOA and comammox Nitrospira. In contrast, nutrient-limited enrichment directly from soil, and nutrient-limited sub-cultivation of batch enrichments consistently yielded high enrichments of Nitrosocosmicus-affiliated AOA associated with multiple canonical nitrite-oxidizing Nitrospira strains, whereas AOB numbers dropped below 0.1% and comammox Nitrospira were lost completely. Our results reveal competitiveness of Nitrosocosmicus sp. under nutrient limitation, and a likely more complex or demanding ecological niche of soil comammox Nitrospira than simulated in our nutrient-limited chemostat experiments.